Plant tissue culture : (Academic Press, 1981)
Plant Tissue Culture, provides laboratory exercises in plant tissue culture that demonstrate major educational concepts. The experiments can be conducted with a variety of plant materials that are available year round from easily accessible sources. This course book will give students diverse learning experiences in a semester course. New and experienced plant scientists in agriculture, university, and industry settings will also find this concise manual to be of great value.